2014
DOI: 10.1080/08927014.2014.974576
|View full text |Cite
|
Sign up to set email alerts
|

Diatom community structure on in-service cruise ship hulls

Abstract: Diatoms are an important component of marine biofilms found on ship hulls. However, there are only a few published studies that describe the presence and abundance of diatoms on ships, and none that relate to modern ship hull coatings. This study investigated the diatom community structure on two in-service cruise ships with the same cruise cycles, one coated with an antifouling (AF) system (copper self-polishing copolymer) and the other coated with a silicone fouling-release (FR) system. Biofilm samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 16 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…This frequency of hull cleaning is insufficient to reduce the risk of invasive species and may leave settlement cues from macrofouling organisms that influence subsequent settlement (Ralston & Swain 2014). It has also been shown that the nature and quantity of biofilms present differs among the types of antifouling (AF) coatings (Zargiel et al 2011;Hunsucker et al 2014;Muthukrishnan et al 2014;Zargiel & Swain 2014). Specifically, the age, composition, and thickness of a biofilm have been shown to influence the organisms that subsequently settle on a coated surface as well as their adhesion and growth properties (Dobretsov et al 2013;Mieszkin et al 2013;Shikuma et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…This frequency of hull cleaning is insufficient to reduce the risk of invasive species and may leave settlement cues from macrofouling organisms that influence subsequent settlement (Ralston & Swain 2014). It has also been shown that the nature and quantity of biofilms present differs among the types of antifouling (AF) coatings (Zargiel et al 2011;Hunsucker et al 2014;Muthukrishnan et al 2014;Zargiel & Swain 2014). Specifically, the age, composition, and thickness of a biofilm have been shown to influence the organisms that subsequently settle on a coated surface as well as their adhesion and growth properties (Dobretsov et al 2013;Mieszkin et al 2013;Shikuma et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Biofilm growth dominated by diatoms has been reported on ship hulls coated with foul release coatings [9]. Some natural bioactive compounds have also been reported for their anti-algal biofilm potential [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae are significant contributors of biofilm growth in case of marine environments [8]. The biofilms formed on ship hulls are often dominated by diatoms [9]. The metabolic activities of photosynthetic microalgae can promote corrosion of stainless steel via release of oxygen and hydrogen peroxide [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations